2013
DOI: 10.1007/s00415-013-6944-9
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal ghrelin secretion contributes to gastrointestinal symptoms in multiple system atrophy patients

Abstract: Patients with multiple system atrophy (MSA) often have evidence of compromised gastrointestinal motility. Ghrelin is a gut hormone that influences gastrointestinal motility in humans. The aim of this study was to determine whether ghrelin secretion is affected in MSA patients, and to investigate the relation between ghrelin secretion and gastrointestinal symptoms. Plasma levels of active ghrelin and unacylated ghrelin were measured in patients with MSA (n = 30), other atypical parkinsonian disorders including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To date, multiple brain-gut peptides have been identified (38)(39)(40)(41)(42), including somatostatin, gastri), cholecystokinin, vasoactive intestinal peptide, motilin, substance P and ghrelin. Ghrelin is an endogenous ligand of the growth hormone secretagogue receptor, and has been shown to be important in several diseases (26)(27)(28)(29)(30). However, the dynamic changes in serum levels of ghrelin during the early stages of ICH, and its time-dependent correlation with SIM, have not been reported previously.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, multiple brain-gut peptides have been identified (38)(39)(40)(41)(42), including somatostatin, gastri), cholecystokinin, vasoactive intestinal peptide, motilin, substance P and ghrelin. Ghrelin is an endogenous ligand of the growth hormone secretagogue receptor, and has been shown to be important in several diseases (26)(27)(28)(29)(30). However, the dynamic changes in serum levels of ghrelin during the early stages of ICH, and its time-dependent correlation with SIM, have not been reported previously.…”
Section: Discussionmentioning
confidence: 98%
“…There has been increasing interest regarding its potent effects on gastric emptying and GI motility. A number of studies have shown that the peptide is vital in protecting against GI dysmotility in various diseases, including multiple system atrophy (26), systemic sclerosis (27), stress (28), shock (29), diabetes (30) and brain events (11)(12)(13)(14). However, the protective role and underlying mechanisms of ghrelin in ICH-induced small intestinal dysmotility remain to be elucidated, which has limited systemic treatment paradigms for pediatric ICH.…”
Section: Introductionmentioning
confidence: 99%